Hambatan Keberhasilan Pelaksanaan Inisiasi Menyusu Dini (IMD) pada Ibu Bersalin di Rumah Sakit Umum Pusat Sanglah Denpasar - Ni Nyoman Sukarti; I Gusti Ayu Trisna Windiani; Desak Yuli Kurniati (Poltekkes Kemenkes Denpasar, 2020)
The problem of neonatal mortality is still a priority in Indonesia because 59% has contributed to infant mortality. Early breastfeeding (IMD) and exclusive breastfeeding is one of the intervention programs to reduce neonatal and infant mortality. This study aims to explore the implementation of early breastfeeding initiation at the Sanglah Central General Hospital Denpasar using qualitative methods. Data were obtained through in-depth interviews with 5 specialist doctors, 3 mothers giving birth and 5 focus group disscusion activities with 22 midwives. Data collection was carried out from October 2018 to January 2019. Data were analyzed thematically and presented using a narrative approach. The main themes that emerged in this study were 3, namely the knowledge of health workers related to the IMD program, supporting infrastructure facilities from hospitals for the implementation of IMD, and the implementation of the IMD program at Sanglah Hospital. The results of this study indicate that the implementation of IMD has not been carried out properly and correctly. The low knowledge of officers about IMD regulation and the motivation of officers in implementing IMD in mothers. The implementation has also not been supported by information media such as posters, photos, leaflets, booklets and counseling books. Implementation needs to be further enhanced by campaigning for early breastfeeding initiation to increase knowledge both of health workers and the wider community.